Circulation patterns in the Gulf of Finland from daily to seasonal timescales. Issue 1 (1st January 2019) - Westerlund, Antti; Tuomi, Laura; Alenius, Pekka; Myrberg, Kai; Miettunen, Elina; Vankevich, Roman E.; Hordoir, Robinson
Abstract: We studied circulation patterns in the Gulf of Finland (GoF), an estuary-like sub-basin of the Baltic Sea. Circulation patterns in the GoF are complex and vary from season to season and year to year. Estuarine circulation in the gulf is heavily modified by many factors, such as wind forcing, topography and geostrophic effects. Based on a 7-year run of the NEMO 3D hydrodynamic model with a 500 m horizontal resolution, we analysed seasonal changes of mean circulation patterns. We found that there were clear seasonal differences in the circulation patterns in the GoF. Features that moved or changed direction from season to season were damped or hidden in the averages. To further study these differences, we also carried out a self-organising map (SOM) analysis of currents for several latitudinal sections. The results of the SOM analysis emphasised the estuary-like nature of the GoF. Circulation changed rapidly from normal estuarine circulation to reverse estuarine circulation. The dominant southwesterly winds supported the reversal of the estuarine circulation. Both normal and reversed estuarine circulation were roughly as common in our data. The SOM analysis also demonstrated how the long-term cyclonic mean circulation field and the average salinity field emerged from the interaction of normal and reversed estuarine circulation.